Analisis Gaya Bahasa, Psikologi dan Nilai-Nilai Pendidikan dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Agus Darmuki (Jurnal Penelitian Pendidikan, 2014)
This research aims at revealing a clear depiction of figurative language, literaturepsychology and educational values of Novel Small Letters to God, Davonar Agnes’ work. It iskind of descriptive qualitative research method. And the source of data is by using NovelSmall Letters to God, of Davonar Agnes’ work. The data which is used is the result of theresearched annotation in the form of sentences containing figurative language andeducational values of Novel Small Letters to God. Furthermore, the data collection wascarried out by using literature technique or document. The analysis activity is begun fromdata reduction that allows the researcher to discharge and enter the useful data as well astriangulation which allows researcher to acquire the validity of the data. Thus, the reduceddata as well as triangulation will provide a clear depiction and facilitate researchers forcollecting the further data. Based on the research findings, it can be concluded that NovelSmall Letters To God has psychology, figurative language and educational values. NovelSmall Letters To God, of Agnes Davonar’s work is found to have id, ego and super-ego. Thisnovel uses figurative language as follows: hyperbole, personification, climax, irony,antithesis, satire, litotes, anastrophe, paronomasia, periphrasis, paralipsis, apostrophe, andcontains the educational values, including religious, moral, and social value.